Cruise Management Information and Decision Support Systems - Papathanassis, Alexis; Breitner, Michael H.; Schoen, Cornelia; Guhr, Nadine; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2012)
Increasingly, cruise operators are utilising information and communication technologies (ICTs) to improve service-effectiveness and process efficiency, both on- and off-board. Therefore, it is worth initiating a discussion on the potential and challenges ICTs entail for both cruise operators$1 (Bback-offices and for cruisers$1 (Bconsumption experiences. This book documents the proceedings of the 1st e-Cruising Conference (Bremerhaven, Germany), which was aimed at discussing the possibilities and applicability of ICTs and mobile services in various aspects of cruise operations. Following a rigorous double-blind review, the best papers were chosen to be incorporated in this volume.s
Keywords: Business; Marketing; Business and Management; Marketing; Electronic books